1952
DOI: 10.1021/ac60072a020
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Typical Grape Brandy Fusel Oil

Abstract: °Paste titration method for acidity. de-ashed oxidized starches based on the corrected acidity is believed to be a better approximation to the "real carboxyl content" than calculations based on the uncorrected acidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

1957
1957
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 12 publications
(9 reference statements)
2
14
0
1
Order By: Relevance
“…Apparently, consistent with their high affinity (V max /K m ) for 2-oxo-butanoate found in cell extracts, pyruvate decarboxylase can compete efficiently for this substrate in vivo with isoleucine biosynthesis. This high affinity, combined with the high-level expression of pyruvate decarboxylase in anaerobic, fermentative yeast cultures (54), provides an adequate explanation for the occurrence of low concentrations of n-propanol in a wide range of yeast-based alcoholic beverages (i.e., wine, cider, and brandy [43,50,63]). Pyruvate decarboxylase is also likely to be responsible for the production of propanoate by aerobic S. cerevisiae cultures (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, consistent with their high affinity (V max /K m ) for 2-oxo-butanoate found in cell extracts, pyruvate decarboxylase can compete efficiently for this substrate in vivo with isoleucine biosynthesis. This high affinity, combined with the high-level expression of pyruvate decarboxylase in anaerobic, fermentative yeast cultures (54), provides an adequate explanation for the occurrence of low concentrations of n-propanol in a wide range of yeast-based alcoholic beverages (i.e., wine, cider, and brandy [43,50,63]). Pyruvate decarboxylase is also likely to be responsible for the production of propanoate by aerobic S. cerevisiae cultures (35).…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with previous studies of norvaline production in E. coli (6), such a pathway could encompass the carbon chain elongation of 2-oxobutanoate by the leucine biosynthesis enzymes Leu4/9, Leu2, and Leu1. Alternatively, the frequent occurrence of low con-centrations of n-butanol in fermented beverages (50,63) may reflect the pyruvate decarboxylase-mediated decarboxylation of plant-derived 2-oxo-pentanoate by S. cerevisiae. Extensive metabolic engineering of S. cerevisiae for the expression of a Clostridium n-butanol pathway (49) resulted in n-butanol titers that were 2 orders of magnitude lower than those observed for norvaline-grown batch cultures of a wild-type S. cerevisiae strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A carefully weighed amount (87.5 9.) of absolute ethanol (>99.95%) was added to the essence at this point to remove any remaining traces of water as the ethanol-water azeotrope (22) in the subsequent distillation. Distillation was then continued through the micro Podbielniak column over a period of several days until the remaining material in the boiler started to darken from decomposition, during which time 480 g. of essence, in addition to the added ethanol above, had been collected as distillate.…”
Section: Methodsmentioning
confidence: 99%
“…The alcohols present in approximately 15 mg. of each distillation fraction were converted to the 3,s-dinitrobenzoate derivatives by reaction with 3,s-dinitrobenzoyl chloride in anhydrous pyridine (22). The crude derivative preparation was then chromatographed (25), the bands eluted and identified by means of melting points and mixed melting points with known derivatives.…”
Section: Absorbtion Of 1% Bromine In CCL Solutionmentioning
confidence: 99%
“…Penniman et al (1937), through colorimetric methods, Schicktanz et al (1939) using azeotropic distillation, and Ikeda et al (1956) from chromatographic analysis, were able to identify the main alcohols (C2 to C5) present in fusel oil from different sources. Marvel and Hager (1924) and Webb et al (1952) found esters derived from short-chain alcohols, mainly i-amyl alcohol, and some carboxylic acids (C10 to C20). Results from comprehensive studies developed with improved analytic techniques, such as mass spectrometry (MS), high resolution gaseous chromatography (HRGC), headspace solid phase microextraction (SPME), among others, have shown a higher amount of components in different fractions of fusel oil.…”
Section: Introductionmentioning
confidence: 99%